Cathepsin K inhibition by VBX1000 alleviates canine periodontitis - Gawor, Jerzy; Gawor, Daria Ziemann; Druet, Isabelle; Salindre, Julien; Gajosz, Alicja; Kowalczyk, Paweł; Dam, Noémie; Tierny, Dominique; Dubruque, Matthieu; Hanf, Rémy (Frontiers in Veterinary Science, 2025)
IntroductionThe efficacy and safety of a novel cathepsin K inhibitor, VBX1000, were evaluated in client-owned dogs suffering from periodontal disease.MethodsThis open-label study recruited twenty dogs (n = 20) with at least 3 teeth at stage 2 or 3 of periodontal disease. Dogs were orally treated once-a-day with VBX1000 (25 mg/kg or 50 mg/kg, n = 10 per group) for 60 days, and then with 50 mg/kg once-a-day for an additional 30 days. The first objective was to assess evolution compared to pre-treatment of plasma carboxy-terminal telopeptide of collagen type 1 (CTX1) used as a marker of target engagement and bone resorption. In each evaluated tooth (n = 60; three teeth per dog), evolution counter to baseline of clinical attachment loss (CAL), periodontal probing depth (PPD), and bleeding on probing index (BPI) were evaluated The effects of cathepsin K inhibitor on alveolar bone defects were assessed with intraoral dental radiography (DR) performed at inclusion and at the end of the treatment period. A confirmatory analysis was performed in a subpopulation (n = 10 dogs; 30 teeth) using the cone beam computed tomography scan (CBCT) imaging technique.ResultsThroughout the treatment period, VBX1000 was well tolerated. At Day60, plasma CTX1 was significantly and similarly reduced compared with baseline (p < 0.05) in the two groups. At the end of the treatment period (at Day90) in the total population (n = 20), plasma CTX1 was 0.10 ± 0.04 ng/mL relative to 0.26 ± 0.20 ng/mL at baseline (p < 0.001). DR before and after treatment showed decreases in width (n = 60 teeth; three teeth/dog; p < 0.0001), depth (p < 0.05), and height of bone defects measured between the root and the maxillary bone. These effects on bone defects were confirmed in a subpopulation analyzed by CBCT. At the end of the treatment period, clinical attachment loss (CAL) was reduced relative to pretreatment: 2.87 ± 1.73 mm compared to 3.86 ± 2.06 mm (n = 60; p < 0.0001). Likewise, the periodontal probing depth (PPD) was reduced 2.71 ± 1.03 mm compared to 3.69 ± 1.23 mm (n = 60, p < 0.0001).ConclusionThe findings support the inhibition of cathepsin K by VBX1000 as a new therapeutic approach for mild-to-moderate periodontal disease in dogs. A randomized, double blinded placebo-controlled trial in dogs should confirm the potential of VBX1000 in this indication.